HDL (High-Density Lipoprotein) Cholesterol Efflux Capacity Is Associated With Incident Cardiovascular Disease in the General Population - Ebtehaj, Sanam; Gruppen, Eke G; Bakker, Stephan J L; Dullaart, Robin P F; Tietge, Uwe J F (Arteriosclerosis, thrombosis, and vascular biology, 2019)
Focus is shifting from HDL-C (high-density lipoprotein cholesterol) as predictive biomarker for cardiovascular disease (CVD) towards antiatherogenic HDL functionalities. Still, limited data exist on the prospective association of HDL function metrics with CVD events. The current work aimed to determine, if baseline HDL-C efflux capacity (CEC) is associated with future CVD events in the general population. Approach and Results: We performed a prospective study among participants of the PREVEND (Prevention of Renal and Vascular End-stage Disease) cohort (follow-up, 12 years). From the overall n=8592 subjects 325 with previous CVD events were excluded; of the remaining 8267 eligible participants all subjects with new CVD events during follow-up were selected and individually matched to controls for age, sex, smoking status, and HDL-C levels. CEC at baseline was quantified using human THP-1-derived macrophage foam cells and apolipoprotein B-depleted plasma. Despite identical HDL-C and apoA (apolipoprotein)-I levels between cases (n=351) and controls (n=354) CEC was significantly lower in cases (0.93±0.29 versus 1.01±0.24 arbitrary units; P<0.001). In all subjects combined, CEC correlated positively with HDL-C and apoA-I and negatively with body mass index, hsCRP (high-sensitivity C-reactive protein), and urinary albumin excretion. CEC was inversely associated with incident CVD events, both expressed per quartile and per 1 SD change (odds ratio, 0.73; 95% CI, 0.62-0.86; P<0.001); this association remained significant after adjustments for HDL-C, hsCRP, kidney function, and several other clinical covariates. Combined these data demonstrate that in the general population baseline CEC is significantly associated with the future development of CVD events independent of HDL-C and apoA-I plasma levels.